Chapter Application of Green Extraction Techniques for Natural Additives Production - Carreira-Casais, Anxo; Lourenço-Lopes, Catarina; Otero, Paz; Carpena Rodriguez, María; Gonzalez Pereira, Antia; Echave, Javier; Soria-Lopez, Antón; Chamorro, Franklin; Ángel Prieto, Miguel; Simal-Gandara, Jesus (InTechOpen, 2024)
undefined